Odpowiedź :
Odpowiedź:
1)
2d-4 = -d-5
2d+d=-1
3d=-1
d=-1/3
2) -3x+2=7+4x
-7x=5
x=-5/7
3)r+6 = 2r+7
r=-1
4) 5t-6 =3t-10
2t=-4
t=-2
Szczegółowe wyjaśnienie:
Odpowiedź:
1) 2d -4 = - d -5
2d+d= -5 +4
3d= -1 /: 3
d= - 1/3
spr... 2*(-1/3) -4= - (-1/3) -5
-2/3-4= 1/3-5
-4 i 2/3= -4 i 2/3
L=P
2) -3x +2 = 7 +4x
-3x-4x= 7-2
-7x= 5 /:7
x= - 5/7
spr... -3 *(-5/7) +2= 7 + 4*(-5/7)
15/7 +2= 7 -20/7
2 i 1/7 +2= 7- 2 i 6/7
4 i 1/7= 6 i 7/7- 2 i 6/7
4 i 1/7 = 4 i 1/7
L=P
3.) r+6 = 2r +7
r-2r= 7 -6
-r= 1 /*(-1)
r= -1
spr... -1 +6= 2*(-1)+7
5= -2+7
5=5
L=P
4) 5t -6 = 3t -10
5t-3t = - 10+6
2t= -4 /:2
t= - 2
spr... 5*(-2) -6= 3*(-2) -10
-10-6= -6-10
-16= - 16
L=P
Szczegółowe wyjaśnienie: